Interdependency between Plant Resources and the Tarao Community of Chandel District, Manipur, in Treating Ailments - Singh, Surchand; Fatima, Tahseen; Manoranjan Sharma, H.; Dinendra Sharma, L. (Indian Forester, 2026)
The present study investigates the interdependency between the Tarao community of Chandel district, iVianipur, and forest resources in the treatment of various aiiments. Conducted from April to September 2022, the study aimed to document the traditional i(nowledge of medicinal plant use, identify commonly utilized plant species, and analyze patterns of plant parts used and aliments treated. Ethnobotanlcal data were collected through structured Interviews, participatory observations, and field surveys with community elders and local healers. A total of 42 plant species were recorded, with herbs constituting the majority (47.6%), followed by trees (28.6%), shrubs (16.7%), and climbers (7.1%). Leaves were the most frequently used plant part (59.5%), followed by fruits (28.6%), barit (23.8%), rhizomes (21.4%), and whole plants (19.0%). The documented species were primarily used to treat digestive disorders (52.4%), sidn and wound healing (42.9%), and fever or respiratory illnesses (33-35%). The Tarao community employs preparation methods such as decoctions, infusions, and pastes, guided by traditional ecological knowledge passed orally across generations. The study highlights that the choice of plant species and sustainable harvesting practices are strongly Influenced by cultural beliefs, spiritual values, and ecological awareness. However, threats such as deforestation, over-exploitation, and erosion of indigenous itnowiedge pose challenges to the continuity of these practices. The findings underscore the importance of integrating community-based forest management with scientific validation of ethnomedicinal knowledge. Preserving this interdependency can safeguard cultural heritage, maintain biodiversity, and contribute to sustainable healthcare systems in resource-limited settings.